Relationships between Parental Education and Overweight with Childhood Overweight and Physical Activity in 9–11 Year Old Children: Results from a 12-Country Study - Muthuri, Stella K.; Onywera, Vincent O.; Tremblay, Mark S.; Broyles, Stephanie T.; Chaput, Jean-Philippe; Fogelholm, Mikael; Hu, Gang; Kuriyan, Rebecca; Kurpad, Anura; Lambert, Estelle V.; Maher, Carol; Maia, José; et al. (PLOS ONE, 2016)
Background Globally, the high prevalence of overweight and low levels of physical activity among children has serious implications for morbidity and premature mortality in adulthood. Various parental factors are associated with childhood overweight and physical activity. The objective of this paper was to investigate relationships between parental education or overweight, and (i) child overweight, (ii) child physical activity, and (iii) explore household coexistence of overweight, in a large international sample. Methods Data were collected from 4752 children (9–11 years) as part of the International Study of Childhood Obesity, Lifestyle and the Environment in 12 countries around the world. Physical activity of participating children was assessed by accelerometry, and body weight directly measured. Questionnaires were used to collect parents’ education level, weight, and height. Results Maternal and paternal overweight were positively associated with child overweight. Higher household coexistence of parent-child overweight was observed among overweight children compared to the total sample. There was a positive relationship between maternal education and child overweight in Colombia 1.90 (1.23–2.94) [odds ratio (confidence interval)] and Kenya 4.80 (2.21–10.43), and a negative relationship between paternal education and child overweight in Brazil 0.55 (0.33–0.92) and the USA 0.54 (0.33–0.88). Maternal education was negatively associated with children meeting physical activity guidelines in Colombia 0.53 (0.33–0.85), Kenya 0.35 (0.19–0.63), and Portugal 0.54 (0.31–0.96). Conclusions Results are aligned with previous studies showing positive associations between parental and child overweight in all countries, and positive relationships between parental education and child overweight or negative associations between parental education and child physical activity in lower economic status countries. Relationships between maternal and paternal education and child weight status and physical activity appear to be related to the developmental stage of different countries. Given these varied relationships, it is crucial to further explore familial factors when investigating child overweight and physical activity.